HOW DID VIRGIL READ THEOCRITUS? - Hatzikosta, Styliani (Myrtia, 2001)
This paper will try to support the thesis that Virgil read in Theocritus’ so-called bucolic poems the poet’s renunciation of bucolic poetry as inviable expression of contemporary society. He agreed with it and expressed his agreement chiefly in the Eclogues , composed in a period of political turbulence and social unrest. The support of this thesis is based on the examination of characteristic passages of the two poets and of few other passages which, I believe, point to this direction; the examination focuses on the ways Virgil imitated and adapted his literary model.